2020
DOI: 10.5194/acp-20-11979-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between ground-based observations and NAVGEM-HA analysis data in the mesosphere and lower thermosphere region

Abstract: Abstract. Recent studies have shown that day-to-day variability of the migrating semidiurnal solar (SW2) tide within the mesosphere and lower thermosphere (MLT) is a key driver of anomalies in the thermosphere–ionosphere system. Here, we study the variability in both the amplitude and phase of SW2 using meteor radar wind and lidar temperature observations at altitudes of 75–110 km as well as wind and temperature output from the Navy Global Environmental Model – High Altitude (NAVGEM-HA), a high-altitude meteor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 93 publications
7
61
0
Order By: Relevance
“…The DOY 265 amplitude peak appears to be an enhancement superimposed on the broad wintertime maximum. There are a number of mechanisms that can excite a time-localized forcing of TW3, such as non-linear wave-wave interactions and diurnal tide and gravity wave interactions (Teitelbaum et al, 1989;Miyahara and Forbes, 1991). Whether conditions are favorable for any such mechanisms to come into effect around DOY 265 remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…The DOY 265 amplitude peak appears to be an enhancement superimposed on the broad wintertime maximum. There are a number of mechanisms that can excite a time-localized forcing of TW3, such as non-linear wave-wave interactions and diurnal tide and gravity wave interactions (Teitelbaum et al, 1989;Miyahara and Forbes, 1991). Whether conditions are favorable for any such mechanisms to come into effect around DOY 265 remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting analyses near the model top are heavily influenced by this imposed diffusion. Therefore, in this study we limit our focus to altitudes below 95 km geometric altitude, where 200 previous validation studies (e.g., McCormack et al, 2017;Dhadly et al, 2018;Stober et al, 2020) have shown NAVGEM-HA to produce reliable results. The NAVGEM-HA system produces analyses every 6 hours, and these fields are supplemented by 3-hourly forecast fields produced by the system as part of the 4DVAR framework, providing an effective 3-hourly sampling rate for the extraction of tidal signatures in the horizontal wind and temperature fields.…”
mentioning
confidence: 99%
“…At mid-and polar latitudes non-migrating tides can be generated by various processes such as latent heat release, nonlinear interactions with stationary planetary waves (Yamashita et al, 2002;Smith et al, 2007;Murphy et al, 2009;Miyoshi et al, 2017) and other tidal modes, variations in the mean background wind and temperature field, and gravity wave breaking or dissipation regions (Fritts et al, 2006). Furthermore, there were some studies investigating SSW as a potential cause to excite the westward propagating semidiurnal tides with wavenumbers 1 and 3 (Du et al, 2007;Liu et al, 2010b;Stober et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric mean winds and tides are analyzed using the ASF, which is described in more detail in Baumgarten and Stober (2019) and Stober et al (2020a) and was already applied in several studies (Stober et al, 2017;Pokhotelov et al, 2018;Wilhelm et al, 2019;Stober et al, 2020b) to decompose MR winds in daily mean winds, diurnal and semidiurnal tides for the zonal and meridional components, respectively. The technique is implemented based on least square fits with full error propagation, which permits to apply the algorithm to unevenly sampled data with data gaps.…”
Section: Data Analysis Of Mean Winds and Atmospheric Tidesmentioning
confidence: 99%
See 1 more Smart Citation